Prostaglandin E2 Secreted by Thyroid Cancer Cells Contributes to Immune Escape Through the Suppression of Natural Killer (NK) Cell Cytotoxicity and NK Cell Differentiation - Park, Arum; Lee, Yunhee; Kim, Mi Sun; Kang, Young Ju; Park, Young-Jun; Jung, Haiyoung; Kim, Tae-Don; Lee, Hee Gu; Choi, Inpyo; Yoon, Suk Ran (Frontiers in Immunology, 2018)
Natural killer (NK) cells play important roles in immune surveillance. However, the tumor microenvironment suppresses NK cell function and allows cancer cells to evade immune detection. In this study, we investigated whether the thyroid cancer cell microenvironment has this effect on NK cells. We found that prostaglandin (PG) E2 produced by thyroid cancer cells suppressed the cytolytic activity of NK cells by inhibiting the expression of the natural cytotoxicity receptors NKp44 and NKp30 and the death receptor tumor necrosis factor-related apoptosis-inducing ligand. PGE2 and cyclooxygenase-2 were highly expressed in thyroid cancer cells; moreover, anaplastic thyroid cancer cells released higher amounts of PGE2 than the papillary subtype, which was associated with suppression of NK cell-inducing nuclear factor-κB and mitogen-activated protein kinase/extracellular signal-regulated kinase pathways via PGE2 receptor (EP)2 and EP4 expressed on the NK cell surface. In addition, PGE2 inhibited the differentiation of NK cells and reduced their cytotoxicity against target cells. These results indicate that PGE2 promotes thyroid cancer progression by inhibiting NK cell differentiation and cytotoxicity. Thus, therapeutic strategies that target PGE2 in thyroid cancer could potentiate the immune response and improve patient prognosis.